(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The socio-historical prerequisites for the emergence of the idea of gender equality in Makola emphasize that the issue of women is inextricably linked with society, social relations, Nations, states, culture and civilisations. The development of the concept of gender is also associated with the transition of socio-historical processes from one stage to another, therefore, the idea is based on the fact that the concept of gender does not represent only women’s interests gender-a social aspect of relations between women and men, manifested in all spheres of life and activity of society, including politics